A Comparative Study of Attitudes toward English as A Foreign Language Learning between Upper Secondary Students in Science-Mathematics and Arts-Language Programs at The Demonstration School Of Ramkhamhaeng University, Thailand - Manachon, Nataporn; Eamoraphan, Suwattana (Scholar: Human Sciences, 2017)
This study focused on three objectives. The first objective was to determine the level of upper secondary students’ attitudes toward English as a foreign language learning in Science-Mathematics at the Demonstration School of Ramkhamhaeng University. The second objective was to determine the level of upper secondary students’ attitudes toward English as a foreign language learning in Arts-Language at the Demonstration School of Ramkhamhaeng University. The third objective was to compare the students’ attitude toward English as a foreign language learning between students in Science-Mathematics and Arts-Language programs. There were four hundred and thirty one upper secondary students at the Demonstration School of Ramkhamhaeng University participated in academic year 2015. The study used two groups of students that consist of Science-Mathematics and Arts-Language students. In conclusion, the findings indicated that Thai upper secondary students in Science-Mathematics and Arts-Language programs at the Demonstration School of Ramkhamhaeng University had positive attitudes toward English as a foreign language learning. The research result also reviewed that there was no significant difference between the students’ attitudes toward English as a foreign language learning. The study concludes with recommendations for practice and for future research.